Anti-erosion aluminum oxide-silicon carbide refractory material for hydrogen-based furnace and preparation method of anti-erosion aluminum oxide-silicon carbide refractory material

By optimizing the proportion and preparation process of alumina-silicon carbide refractory materials, the problem of prone to oxidation and erosion under the conditions of hydrogen-based vertical furnaces is solved, and higher pressure, anti-discounts, and anti-erosion are achieved Performance has extended the service life of the equipment and reduced the cost.

CN119371210APending Publication Date: 2025-01-28ZHENGZHOU ANNEC IND

Patent Information

Application Number
CN202411483755.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing alumina-silicon carbide refractory materials are easily oxidized under the conditions of hydrogen-based vertical furnaces and are eroded by H2 and CO, resulting in a reduction in the compressive strength and wear resistance, affecting the service life of hydrogen-based vertical furnaces.

Method used

A specific proportion of alumina-silicon carbide refractory materials, including coarse silicon carbide powder, brown corundum, blue spar, silicon carbide powder, aluminum aluminum micro powder, graphite, white mud, and phosphate aluminum and other raw materials. Preparation of material materials to improve the resistance of materials.

Benefits of technology

It significantly improves the high temperature resistance, folding strength, thermal stability, and anti -H2, CO erosion performance of the refractory material, extend the service life of the hydrogen -based vertical furnace, and reduce the production cost.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides an anti-erosion aluminum oxide-silicon carbide refractory material for a hydrogen-based furnace and a preparation method of the refractory material. The refractory material comprises the following raw materials in parts by mass: 30-40 parts of coarse silicon carbide powder with the particle size of 3-1mm; 20-30 parts of fused white corundum with a particle size of less than 1-0 mm; 3-10 parts of kyanite with a particle size of less than 0-0.2 mm; 10-20 parts of fine silicon carbide powder with the particle size lower than 0.074 mm; 5-10 parts of alumina micro powder with a particle size of less than 3 [mu] m; 1-5 parts of graphite with a particle size of less than 5 [mu] m; 1-5 parts of white mud with a particle size of less than 0.088 mm; 1-10 parts of solid aluminum dihydrogen phosphate; and 1-2 parts of sodium hexametaphosphate. The alumina-silicon carbide refractory material has the characteristics of low expansion coefficient, high-temperature compression resistance, high breaking strength, good thermal stability, stable chemical performance, wear resistance, H2 and CO erosion resistance and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of refractory materials, in particular to an anti-corrosion aluminum oxide-silicon carbide refractory material for hydrogen-based furnaces and a preparation method thereof. Background Art

[0002] Alumina-silicon carbide refractory is a special refractory with excellent physical and chemical properties, and can be used under various extreme conditions. It can be widely used in industrial production where other ordinary refractory materials and metal products cannot meet the use requirements. Because ordinary alumina-silicon carbide refractory is easily oxidized and corroded by H2 and CO under the working conditions of hydrogen-based vertical furnace, its compressive strength and wear resistance are reduced, which affects the life of hydrogen-based vertical furnace.

[0003] Therefore, in order to extend the service life of the hydrogen-based vertical furnace, it is necessary to develop an alumina-silicon carbide refractory material for the hydrogen-based vertical furnace that is resistant to H2 and CO corrosion. Summary of the invention

[0004] In order to solve the deficiencies in the prior art, the present invention provides a corrosion-resistant alumina-silicon carbide refractory material for a hydrogen-based furnace and a preparation method thereof. The alumina-silicon carbide refractory material has the characteristics of low expansion coefficient, high high-temperature compressive and flexural strength, good thermal stability, stable chemical properties, wear resistance, and resistance to H2 and CO corrosion.

[0005] In order to achieve the above object, the specific scheme adopted by the present invention is:

[0006] In one aspect, the present invention provides a corrosion-resistant alumina-silicon carbide refractory material for a hydrogen-based furnace, comprising the following raw materials in parts by mass: 30-40 parts of coarse silicon carbide powder with a particle size of 3-1 mm; Brown corundum with particle size less than 1-0mm 20-30 parts; 3-10 parts of kyanite with a particle size less than 0-0.2 mm; 10-20 parts of fine silicon carbide powder with a particle size less than 0.074 mm; 5-10 parts of alumina powder with a particle size less than 3 μm; 1-5 parts of graphite with a particle size below 5μm; 1-5 parts of white mud with particle size less than 0.088mm; 1-10 parts of solid aluminum dihydrogen phosphate; 1-2 parts of sodium hexametaphosphate.

[0007] Preferably, the following raw materials are included in parts by weight: 30-40 parts of coarse silicon carbide powder with a particle size of 3-1 mm; Brown corundum with particle size less than 1-0mm 20-30 parts; 3-8 parts of kyanite with a particle size less than 0-0.2 mm; 10-20 parts of fine silicon carbide powder with a particle size less than 0.074 mm; 5-10 parts of alumina powder with a particle size less than 3um; 1-5 parts of graphite with particle size less than 5um; 1-5 parts of white mud with particle size less than 0.088mm; 5-10 parts of solid aluminum dihydrogen phosphate; 1-2 parts of sodium hexametaphosphate.

[0008] Furthermore, the mass fraction of SiC in the coarse silicon carbide powder or the fine silicon carbide powder is ≥98%, the mass fraction of Al2O3 in the brown corundum is ≥95%, the mass fraction of Al2O3 in the kyanite is ≥56%, the mass fraction of Al2O3 in the alumina powder is ≥99.5%, and the mass fraction of Al2O3 in the white mud is ≥33%.

[0009] On the other hand, the present invention discloses a method for preparing a corrosion-resistant aluminum oxide-silicon carbide refractory material for a hydrogen-based furnace, comprising the following steps: (1) Weigh each raw material according to the formula; (2) Place sodium hexametaphosphate in a beaker, heat to 200°C and keep warm until the sodium hexametaphosphate dissolves into a transparent solution; (3) Place coarse silicon carbide powder, fused brown corundum and kyanite in a stirring device and stir for 1-2 minutes; (4) Mix fine silicon carbide powder, alumina powder, graphite, white mud, and solid aluminum dihydrogen phosphate in a premixer for 1-2 minutes to obtain a fine powder; (5) Add the fine powder obtained in step (4) to the stirring device in step (3), add the transparent solution obtained in step (2), stir for 1-3 minutes, and then simmer for 48 hours to obtain the corrosion-resistant alumina-silicon carbide refractory material.

[0010] It should be noted that in the process of preparing alumina-silicon carbide refractory materials, sodium hexametaphosphate in step (2) is added as a dispersant for refractory materials. Since the amount added is small, it is more uniform to add the solution. In step (5), the obtained fine powder and transparent solution are added to a stirring device and stirred evenly, and then trapped. This is because there are certain impurities in the raw materials of the refractory materials. These impurities react with the aluminum dihydrogen phosphate binder to form a large amount of gas after the reaction. The gas will cause the inside of the refractory material to expand, resulting in a loose structure of the material and a decrease in strength after hardening. The 48h trapped material can fully discharge the gas, thereby improving the deposition density and density.

[0011] The role of each raw material in the present invention is described below. Silicon carbide: SiC can be oxidized into SiO2 during the sintering process, which closes the surface pores of the product. Combined with clay, the material has better sintering properties, so that the resulting product has lower apparent porosity and higher compressive strength, wear resistance, and stable corrosion resistance. Brown corundum: Improve wear resistance. Kyanite: The main chemical composition of kyanite is Al2O3≥56%. Kyanite powder has the characteristic of permanent irreversible expansion at high temperature. When in contact with high-temperature metal liquid, the coating expands in volume due to heat, does not shrink after cooling, and the metal casting shrinks to produce gaps, making it easy for the casting to detach. In the present invention, the kyanite powder begins to decompose at 1100°C in the high-temperature stage, and the decomposition of kyanite intensifies at 1300°C, and a large amount of mullite is generated. The decomposition speed accelerates at 1350°C, and it is completely decomposed at 1450°C, at which time the linear expansion rate is 6%. When the temperature reaches 1500°C, quartz glass and fibrous mullite crystals begin to appear. The formed mullite has high refractoriness and good stability, a small expansion coefficient, is not easy to shrink after cooling, and mullite does not infiltrate with metal solution, and has high chemical corrosion resistance. Alumina powder: promotes matrix sintering, improves strength and wear resistance. Graphite: The graphite powder has a main component of carbon ≥ 90%, has extremely high refractoriness, is volume stable at high temperatures, does not chemically react with molten metal, and has excellent corrosion resistance. White mud: As a soft clay binder, it has good binding properties. Aluminum dihydrogen phosphate: Aluminum dihydrogen phosphate is a thermosetting inorganic salt binder and has the best bonding performance among aluminum phosphate binders. It forms high bonding strength after low-temperature drying. After heat treatment at 350-500℃, it has high mechanical strength, anti-hydration performance and resistance to air flow erosion, which improves the medium and low temperature strength of refractory materials.

[0012] Beneficial effects:

[0013] 1. The pores in the refractory material determine the stability of the refractory material to the corrosive substances. The present invention selects refractory raw materials with high density and low water absorption rate and adopts multi-level batching. Under the condition of appropriately increasing the firing temperature, a refractory material with low porosity is obtained, which has good resistance to H2 and CO gas erosion under the special working conditions of the hydrogen-based vertical furnace.

[0014] 2. The present invention combines 98 silicon carbide with high-strength raw materials such as brown corundum and kyanite to greatly improve the wear resistance of the refractory material and increase the service life of the refractory material.

[0015] 3. The addition of graphite and kyanite in the present invention makes the refractory material have better chemical stability and corrosion resistance, and has good resistance to H2 and CO gas erosion under the special working conditions of hydrogen-based vertical furnace.

[0016] 4. The refractory material of the present invention uses aluminum dihydrogen phosphate as a high-temperature binder, which has strong chemical bonding strength, high temperature resistance and high temperature gas erosion resistance under high temperature conditions.

[0017] 5. The hydrogen-based vertical furnace in the present invention uses alumina-silicon carbide refractory material that resists H2 and CO erosion, which has better high-temperature compressive and flexural strength, good thermal stability and chemical stability, wear resistance and resistance to H2 and CO erosion, and the hydrogen-based vertical furnace has a longer service life. The present invention is easy to construct, does not require firing, has obvious economic benefits, forms a technical advantage for manufacturers, has a higher premium, and has a longer service life for the user unit, diluting the use cost. DETAILED DESCRIPTION

[0018] In order to more clearly understand the technical content of the present invention, the following examples are given in detail. The SiC mass fraction of the coarse silicon carbide powder or fine silicon carbide powder in the raw materials used in the following examples is ≥98%, the Al2O3 mass fraction of the brown corundum is ≥95%, the Al2O3 mass fraction of the kyanite is ≥56%, the Al2O3 mass fraction of the alumina powder is ≥99.5%, and the Al2O3 mass fraction of the white mud is ≥33%.

[0019] Example 1

[0020] The alumina-silicon carbide refractory material for hydrogen-based vertical furnaces resistant to H2 and CO corrosion of the present embodiment is prepared according to the following steps: (1) weighing 40 parts of coarse silicon carbide powder with a particle size of 3-1 mm, 20 parts of brown corundum with a particle size of less than 1-0 mm, 6 parts of kyanite with a particle size of less than 0-0.2 mm, 16 parts of fine silicon carbide powder with a particle size of less than 0.074 mm, 6 parts of alumina powder with a particle size of less than 3 μm, 2 parts of graphite with a particle size of less than 5 μm, 3 parts of white mud with a particle size of less than 0.088 mm, 6 parts of solid aluminum dihydrogen phosphate, and 1 part of sodium hexametaphosphate; (2) Place sodium hexametaphosphate in a beaker, heat to 200°C and keep warm until the sodium hexametaphosphate dissolves into a transparent solution; (3) Place coarse silicon carbide powder, brown corundum and kyanite in a stirring device; (4) Mix fine silicon carbide powder, alumina powder, graphite, white mud, and solid aluminum dihydrogen phosphate in a premixer for 2 minutes to obtain a fine powder; (5) Add the fine powder obtained in step (4) to the stirring device in step (3), add the transparent solution obtained in step (2), stir for 1-2 minutes, and then simmer for 48 hours to obtain the corrosion-resistant alumina-silicon carbide refractory material.

[0021] Example 2

[0022] The alumina-silicon carbide refractory material for hydrogen-based vertical furnaces resistant to H2 and CO corrosion of the present embodiment is prepared according to the following steps: (1) weighing 35 parts of coarse silicon carbide powder with a particle size of 3-1 mm, 23 parts of brown corundum with a particle size of less than 1-0 mm, 6 parts of kyanite with a particle size of less than 0-0.2 mm, 15 parts of fine silicon carbide powder with a particle size of less than 0.074 mm, 6 parts of alumina powder with a particle size of less than 3 μm, 2 parts of graphite with a particle size of less than 5 μm, 3 parts of white mud with a particle size of less than 0.088 mm, 8 parts of solid aluminum dihydrogen phosphate, and 2 parts of sodium hexametaphosphate; (2) Place sodium hexametaphosphate in a beaker, heat to 200°C and keep warm until the sodium hexametaphosphate dissolves into a transparent solution; (3) Place coarse silicon carbide powder, brown corundum and kyanite in a stirring device; (4) Mix fine silicon carbide powder, alumina powder, graphite, white mud, and solid aluminum dihydrogen phosphate in a premixer for 1-2 minutes to obtain a fine powder; (5) Add the fine powder obtained in step (4) to the stirring device in step (3), add the transparent solution obtained in step (2), stir for 2 minutes, and then trap the material for 48 hours to obtain the corrosion-resistant alumina-silicon carbide refractory material.

[0023] Example 3

[0024] The alumina-silicon carbide refractory material for hydrogen-based vertical furnaces resistant to H2 and CO corrosion of the present embodiment is prepared according to the following steps: (1) weighing 40 parts of coarse silicon carbide powder with a particle size of 3-1 mm, 20 parts of brown corundum with a particle size of less than 1-0 mm, 6 parts of kyanite with a particle size of less than 0-0.2 mm, 15 parts of fine silicon carbide powder with a particle size of less than 0.074 mm, 6 parts of alumina powder with a particle size of less than 3 μm, 2 parts of graphite with a particle size of less than 5 μm, 3 parts of white mud with a particle size of less than 0.088 mm, 6 parts of solid aluminum dihydrogen phosphate, and 2 parts of sodium hexametaphosphate; (2) Place sodium hexametaphosphate in a beaker, heat to 200°C and keep warm until the sodium hexametaphosphate dissolves into a transparent solution; (3) Place coarse silicon carbide powder, brown corundum and kyanite in a stirring device; (4) Mix fine silicon carbide powder, alumina powder, graphite, white mud, and solid aluminum dihydrogen phosphate in a premixer for 1 minute to obtain a fine powder; (5) Add the fine powder obtained in step (4) to the stirring device in step (3), add the transparent solution obtained in step (2), stir for 1-2 minutes, and then simmer for 48 hours to obtain the corrosion-resistant alumina-silicon carbide refractory material.

[0025] The laboratory test indicators of the alumina-silicon carbide refractory prepared in Examples 1-3 are shown in Table 1. The standards used for the tests are: GB / T 16555 for chemical analysis, GB / T 7322 for refractoriness, YB / T 5200 for apparent porosity and bulk density, GB / T 3001 for room temperature flexural strength, GB / T 5072 for room temperature compressive strength, GB / T 5988 for heating permanent linear change, and YB / T 5202.1 for the preparation method of amorphous refractory samples.

[0026] Table 1 Performance indicators of alumina-silicon carbide refractory materials prepared in Examples 1-3 Example 1 Example 2 Example 3 Chemical composition, (SiC%) 54 49 55 Apparent porosity, % 19 20 18 <![CDATA[Bulk density, g / cm 3 > 2.4 2.35 2.45 Flexural strength at room temperature, MPa 14 14 16 Compressive strength at room temperature, MPa 80 70 80 <![CDATA[Wear resistance at normal temperature, cm 3 > 6.0 8.0 4.0 Linear change rate after burning 1300×3h, % 0.0~1.0 0~1.5 0.0~0.8 Room temperature flexural strength, MPa, (after CO erosion) 8 8 14 Room temperature compressive strength, MPa, (after CO erosion) 50 40 65 <![CDATA[Flexural strength at normal temperature, MPa, (after H2 erosion)]]> 9 9 15 <![CDATA[Normal temperature compressive strength, MPa, (after H2 erosion)]]> 45 50 69

[0027] As shown in Table 1, the refractory prepared by the formula and method of the present invention has an apparent porosity of less than 20%, a room temperature flexural strength of greater than 14MPa, a room temperature compressive strength of greater than 70MPa, a room temperature flexural strength of not less than 8MP after CO erosion, a room temperature compressive strength of not less than 40MPa after CO erosion, a room temperature flexural strength of not less than 9MPa after H2 erosion, and a room temperature compressive strength of not less than 45MPa after H2 erosion. The process ratio of the present invention shows good resistance to H2 and CO erosion, and can improve the service life of the furnace in the complex working environment of the hydrogen-based vertical furnace, creating good economic benefits. Compared with Examples 1-2, the room temperature compressive strength of the refractory obtained in Example 3 is higher, the porosity is lower, and the expansion rate is small under high temperature conditions, which can ensure the initial use of the refractory under the special working conditions of the hydrogen-based vertical furnace. At the same time, as time increases, its compressive strength decreases less under H2 and CO erosion, and its anti-erosion effect is the best. At the same time, the wear resistance is the best, and it can resist the scouring of high-temperature gas.

[0028] The present invention improves the high-temperature compressive strength, flexural strength, thermal stability, wear resistance and H2, CO erosion resistance of alumina-silicon carbide refractory materials by optimizing the process ratio, greatly prolonging the service life of the hydrogen-based vertical furnace and creating economic value.

[0029] The above is only a preferred embodiment of the present invention, and does not limit the present invention in any form. Any equivalent changes or modifications made according to the essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A corrosion-resistant alumina-silicon carbide refractory material for hydrogen-based furnaces, characterized in that: Contains the following raw materials in parts by weight: 30-40 parts of coarse silicon carbide powder with a particle size of 3-1 mm; 20-30 parts of fused white corundum with particle size less than 1-0mm; 3-10 parts of kyanite with a particle size less than 0-0.2 mm; 10-20 parts of fine silicon carbide powder with a particle size less than 0.074 mm; 5-10 parts of alumina powder with a particle size less than 3 μm; 1-5 parts of graphite with a particle size below 5μm; 1-5 parts of white mud with particle size less than 0.088mm; 1-10 parts of solid aluminum dihydrogen phosphate; 1-2 parts of sodium hexametaphosphate.

2. The corrosion-resistant alumina-silicon carbide refractory material for hydrogen-based furnaces according to claim 1, characterized in that: Contains the following raw materials in parts by weight: 30-40 parts of coarse silicon carbide powder with a particle size of 3-1 mm; 20-30 parts of fused white corundum with particle size less than 1-0mm; 3-8 parts of kyanite with a particle size less than 0-0.2 mm; 10-20 parts of fine silicon carbide powder with a particle size less than 0.074 mm; 5-10 parts of alumina powder with a particle size less than 3um; 1-5 parts of graphite with particle size less than 5um; 1-5 parts of white mud with particle size less than 0.088mm; 5-10 parts of solid aluminum dihydrogen phosphate; 1-2 parts of sodium hexametaphosphate.

3. The corrosion-resistant alumina-silicon carbide refractory material for hydrogen-based furnaces according to claim 1, characterized in that: The mass fraction of SiC in the coarse silicon carbide powder or the fine silicon carbide powder is ≥98%, the mass fraction of Al2O3 in the fused white corundum is ≥99.5%, the mass fraction of Al2O3 in the kyanite is ≥56%, the mass fraction of Al2O3 in the alumina powder is ≥99.5%, and the mass fraction of Al2O3 in the white mud is ≥33%.

4. A method for preparing corrosion-resistant alumina-silicon carbide refractory material for hydrogen-based furnaces, characterized in that: The following steps are involved: (1) Weigh each raw material according to the formula; (2) Place sodium hexametaphosphate in a beaker, heat to 200°C and keep warm until the sodium hexametaphosphate dissolves into a transparent solution; (3) Place coarse silicon carbide powder, fused white corundum and kyanite in a stirring device and stir for 1-2 minutes; (4) Mix fine silicon carbide powder, alumina powder, graphite, white mud and solid aluminum dihydrogen phosphate in a premixer for 1-2 minutes to obtain fine powder; (5) Add the fine powder obtained in step (4) to the stirring device in step (3), add the transparent solution obtained in step (2), stir for 1-3 minutes, and then simmer for 48 hours to obtain the corrosion-resistant alumina-silicon carbide refractory material.

Citation Information

Patent Citations

  • Wear-resistant material for gasification furnace slag taps

    CN104193309A

  • High temperature self-strengthening silicon carbide refractory casting material and production thereof

    CN1235134A

Cited By

  • Furnace lining structure and preparation method thereof

    CN121994027A